Cyclic shear resistance for seismic design, based on monotonic shear models in fib Model Code 2010 and in the 2018 draft of Eurocode 2. (11th November 2019) - Biskinis, Dionysis; Fardis, Michael N.
Abstract: Shear resistance decays during cycling of inelastic deformations, causing flexural plastic hinges to fail in cyclic shear before reaching their ultimate flexural deformation. The monotonic shear model in MC2010 does not work for shear failure after flexural yielding. Accurate, unbiased, lack‐of‐fit‐free prediction of cyclic shear resistance, before or after flexural yielding, is possible, if: (a) inelasticity is considered in the calculation of longitudinal strains at section mid‐depth, through the "equal displacement rule" of Earthquake Engineering; (b) axial forces are taken to contribute to shear resistance with the transverse component of the diagonal strut between member ends; (c) the Eurocode 2 shear model for loads near supports is used for squat members; and (d) minor changes are made to the minimum compression field angle and the concrete strength reduction along it in MC2010, Levels II or III of approximation.